Etiology evaluation of chylothorax in Babol, Northern Iran - Novin Nikbakhsh; Mohammad Zamani; Askari Noorbaran; Ali Naghshineh; Danial Rastergar-Nejad (Babol University of Medical Sciences, 2017)
Background: Chylothorax results from leakage of lymph in the pleural cavity because of thoracic duct injury which is associated with severe metabolic disorders. The aim of this study was to evaluate the rate of chylothorax and its causes among hospitalized patients in Shahid Beheshti Hospital of Babol city, North of Iran. Methods: In this cross-sectional study, all patients with chylothorax admitted to the surgery department of Shahid Beheshti Hospital during 2002-2015 were included. Information including gender, age, duration of symptoms, laboratory findings, causes of disease and the type of treatment were extracted from the patients' records. Results: Of the 42 patients, 27 (64.3%) were men and 15 (35.7%) were women. The mean age of the study population was 51.03±16.95. The most common clinical symptoms were dyspnea (66.7%) and dyspnea with cough (21.4%), respectively. In all patients, the pleural fluid triglyceride level was greater than 110 mg/dl, whereas the presence of lymphatic in pleural fluid was eventful in 18 (42.8%) patients. The causes of the disease were traumatic (54.8%), non-traumatic (38.1%) and unknown (7.1%), which were not significantly correlated with gender. Nineteen (45.2%) patients were operated, 16 (38.1%) patients received supportive therapy, and 7 (16.7%) patients had the treatment of the underlying conditions and then supportive therapy. Conclusion: According to the results, trauma was the most common cause of chylothorax. Therefore, identification and control of the traumatic factors seem to be the steps to prevent and reduce the chylothorax incidence and its complications.